Mucinous adenocarcinoma with superficial stromal invasion and villous adenoma of urachal remnants: a case report. Issue 6 (1st June 2003) - Mazzucchelli, R; Scarpelli, M; Montironi, R
Abstract : This report describes a case of mucinous adenocarcinoma with superficial stromal invasion and villous adenoma originating in the dome of the urinary bladder. Although no urachal remnants were identified, the location suggested urachal derivation. Only two previous cases of urachal adenocarcinoma with features of early stromal invasion associated with a villous tumour have been described.